[Family planning in the 90's ; Bantay gubat ; A miracle in Central Visayas [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Flavier supporting artificial means of birth control; Puerto Princesa City Mayor Edward Hagedorn in his fight against illegal loggers. Investigates how the people in Central Visayas react to the government's project in transforming their devastated area and how the government will convince the Kaingeros to reform.
Family planning in the 90's (15 min.) -- Bantay gubat (13 min.) -- A miracle in Central Visayas (13 min.)
VHS.
Keywords: Birth control -- Philippines; Environmental protection -- Citizen participation. -- Philippines -- Palawan; Kaingeros -- Philippines -- Negros Oriental; Logging -- Philippines -- Palawan; Reforestation -- Philippines -- Negros Oriental